On project based learning approach and future foreign language teachers - Velasco Moreno, Mª Isabel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Although learning English as a Foreign Language is needed all over the world nowadays, it is still difficult for some Spanish students to learn it. Considering that teacher’s decisions on the use of methodologies is essential in class, we look at future teachers. In this study we focus on future teachers’ training as a key element to match theory and practice and bring to Foreign Language (FL) classes innovative approaches such as Project Based Learning (PBL). A recent experienced (2021-22) in the Faculty of Education of Málaga has been analysed and important conclusions have been drawn from results obtained.